Formation of fibrous or granular egg white protein microparticles and properties of the integrated emulsions. (December 2016) - Chang, Cuihua; Niu, Fuge; Gu, Luping; Li, Xin; Yang, Hao; Zhou, Bei; Wang, Junwei; Su, Yujie; Yang, Yanjun
Abstract: This study investigated the potential of egg white protein (EWP) to be developed into a kind of Pickering stabilizer for oil-in-water emulsions. The EWP microparticles were formed by heating at 90 °C for 45 min, followed by homogenization under low pressure. The characteristics and microstructure of microparticles prepared under various pH (3.0, 3.8) and protein concentration (2–10%) were tested. Simultaneously, the properties of Pickering emulsions integrated by EWP microparticles, with fibrous or granular morphology, were investigated. At pH 3.0, the particles may transfer from fibrous structure to granular structure with protein concentration increased or salt addition. At pH 3.8, granular microparticles were formed under various protein concentration. The structure of EWP microparticles were mainly maintained by hydrophobic interactions and hydrogen bondings. The granular particles showed higher surface loading of protein and viscoelastic moduli in the integrated Pickering emulsions. These results have important implications for the formulation and production of emulsion based semi-solid products, using egg white protein as emulsifier and fat substitute. Graphical abstract: Highlights: Morphology of particles depends on ionic strength and protein concentration. Particles structure are maintained by hydrophobic interaction and hydrogen bonding. Granular microparticle behaves higher protein load onto oil-water interface. Emulsions stabilized by granular microparticle shows higher viscoelastic moduli. G′ of semi-solid emulsions increases with oil volume fraction increasing.